2000
DOI: 10.1021/jp000454i
|View full text |Cite
|
Sign up to set email alerts
|

IR and NMR Study of the Chemisorption of Ammonia on Trimethylaluminum-Modified Silica

Abstract: The saturating reaction of ammonia was studied on trimethylaluminum (TMA)-modified porous silica. This reaction step completes a reaction cycle of TMA and ammonia in aluminum nitride growth by atomic layer chemical vapor deposition (ALCVD), a technique based on well-separated saturating gas-solid reactions. The reaction was studied from 423 to 823 K. In addition, the separate reactions of TMA at 423 K and ammonia at 823 K were studied on silica dehydroxylated at 1023 K. The reaction products on the surface wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 43 publications
7
96
0
Order By: Relevance
“…Coordination of 6 to a nearby siloxane oxygen is likely to occur in order to maintain the preferred tetracoordination at Al. This hypothesis is nevertheless consistent with the ability of AlMe 3 /silica to adsorb Lewis bases such as Et 2 O [47] and NH 3 [43,51]. Adsorption may occur by displacement of the coordinated siloxane oxygen atom, instead of being interpreted as evidence for persistent threecoordinate Al sites [47].…”
Section: Proposed Structure Of Alme 3 /Silicasupporting
confidence: 73%
See 4 more Smart Citations
“…Coordination of 6 to a nearby siloxane oxygen is likely to occur in order to maintain the preferred tetracoordination at Al. This hypothesis is nevertheless consistent with the ability of AlMe 3 /silica to adsorb Lewis bases such as Et 2 O [47] and NH 3 [43,51]. Adsorption may occur by displacement of the coordinated siloxane oxygen atom, instead of being interpreted as evidence for persistent threecoordinate Al sites [47].…”
Section: Proposed Structure Of Alme 3 /Silicasupporting
confidence: 73%
“…This assertion was supported by elemental analysis of AlMe 3 adsorbed on silica gel [44]. However, recent studies involving AlMe 3 -saturated MCM-41 [45] and silica gel [43] reported that a substantial amount of (BSiO)AlMe 2 persists in those materials. Finally, a recent solid state NMR study showed that AlMe 3 caused little methylation of a silica surface [29].…”
Section: The Cocatalyst/support Interactionmentioning
confidence: 85%
See 3 more Smart Citations